HISTOLOGICAL PATTERN OF ENDOMETRIAL SAMPLES IN POST- MENOPAUSAL WOMEN WITH ABNORMAL UTERINE BLEEDING - Deeba, Farhat; ., Shaista; Khan, Bushra (Journal of Ayub Medical College Abbottabad, 2016)
Background: Abnormal uterine bleeding is one of the most common clinical problems in gynaecological practice and is an indicator of various underlying disorders. An endometrial biopsy should be done in all women over 35 years with AUB to rule out endometrial cancer or pre-malignant lesion and to initiate treatment. However, wide range of histological patterns on endometrial biopsy offer a diagnostic challenge to practicing pathologists. The objective of this study was to determine histological patterns of endometrium in postmenopausal women with abnormal uterine bleeding. Methods: This cross-sectional study was conducted in the department of obstetrics and gynaecology, Benazir Bhutto Shaheed women and children teaching hospital, Abbottabad from 15/11/2014 to 14/05/2015. This study involved 110 postmenopausal women presenting with abnormal uterine bleeding. A written informed consent was obtained from every patient. Results: The mean age of the patients was 61.60±6.17 years and the mean duration of AUB was 5.20±2.80 years. Most of the patients were para 6 (28.2%) and para 5 (28.2%) followed by para 4 (18.2%) and para 3 (17.3%) while only 8.2% were para 1. The most common histological pattern observed was complex hyperplasia without atypia (30.9%) followed by atrophic endometrium (24.5%), simple hyperplasia (23.6%), malignancy (12.7%), complex hyperplasia with atypia (4.5%) and benign endometrial polyp (3.6%). When stratified the data, there was no significant difference of histological patterns across various age groups (p=.673), duration of AUB (p=.064) and parity (p=.242). Conclusion: The most common histological pattern observed in postmenopausal women with AUB was complex hyperplasia without atypia (30.9%) followed by atrophic endometrium (24.5%), simple hyperplasia (23.6%), malignancy (12.7%), complex hyperplasia with atypia (4.5%) and benign endometrial polyp (3.6%). Keywords: Postmenopausal Women; Abnormal Uterine Bleeding; Histological Endometrial Patterns